Formalization of DSN-MUI Fatwa No. 28/DSN-MUI/III/2002 in Electronic Money Transactions - Kholifah Nur Ayunda; Isman; Lukmanul Hakim; Mamdukh Budiman (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines the compatibility between Bank Indonesia Regulation No. 20/6/PBI/2018 on Electronic Money and DSN-MUI Fatwa No. 28/DSN-MUI/III/2002 on Currency Exchange (Al-Sharf) in the context of digital financial transactions. The objective of this study is to formulate the concept of norms for improving electronic money transactions to align with Shariah principles, particularly regarding the sharf contract. The method used is normative legal research with a qualitative deductive approach. Data was obtained through documentary studies and analyzed using norm interpretation, systematization, and synthesis. The results of the study indicate that the legal aspects of the organizers and the real-time settlement system in Bank Indonesia's regulations are consistent with Sharia principles. However, there are inconsistencies in the placement of float funds in ribawi instruments and the lack of explicit mention of the sharf contract. Digital taqabudh and information system security standards strongly influence the strength or weakness of the DSN-MUI Fatwa's impact on the compliance of Fintech, sharf contracts, and electronic money with Sharia principles. Meanwhile, the implementation of PBI regulations and operational compliance by organizers bridge the gap between the DSN-MUI Fatwa and practices in the field. Mediators help explain how fatwas are translated into technical policies, while moderators determine the extent to which fatwas can be effective in the complex and rapidly changing digital context.